Anatomy of wooden core of ottoman composite archery bows - Gunduz, Gokhan; Yaman, Barbaros; Ozden, Seray; Donmez, Suleyman Cem (Universiti Kebangsaan Malaysia, 2013)
Composite archery bows have been well known and used by Asiatic societies for thousands of years. The Turkish composite bow, made of wood, horn, sinew and glue is one of the most famous and powerful bows in the world. Because of its high draw weight and mechanical efficiency, the Turkish composite bow became a powerful weapon in the Seljuk and the Ottoman empire. In addition to being a powerful weapon of war, at the same time the bow and arrow (archery) continued to be a sport of Ottoman (sultans, state officials, janissaries) until the late Ottoman period. In this study of the Ottoman composite archery bows in the collections of Izmir Ethnography Museum, a small wood sample was investigated on the basis of its wood anatomy. The results showed that it was made of maple wood (Acer sp.) and some of its qualitative and quantitative anatomical properties are presented here. One of the key properties for the identification of maple wood is the helical thickening throughout the body of the vessel element. Helical thickenings in vessel elements in cutting surfaces of maple-wooden core increase the bonding surface between the wood and sinew-horn. In most of the woods preferred traditionally for bow-making, helical thickenings in tracheids, vessel elements or ground tissue fibres should be taken into account at a hierarchy of cellular structures for elucidating the efficiency of Ottoman composite-wooden bow.